2012
DOI: 10.1073/pnas.1206638109
|View full text |Cite
|
Sign up to set email alerts
|

INVOLVED IN DE NOVO 2-containing complex involved in RNA-directed DNA methylation in Arabidopsis

Abstract: At least three pathways control maintenance of DNA cytosine methylation in Arabidopsis thaliana. However, the RNA-directed DNA methylation (RdDM) pathway is solely responsible for establishment of this silencing mark. We previously described INVOLVED IN DE NOVO 2 (IDN2) as being an RNA-binding RdDM component that is required for DNA methylation establishment. In this study, we describe the discovery of two partially redundant proteins that are paralogous to IDN2 and that form a stable complex with IDN2 in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 35 publications
(42 reference statements)
2
94
0
4
Order By: Relevance
“…In silico analysis of telomeric DNA methylation Data from different genome-wide bisulfite sequencing studies were analyzed (Schmitz et al 2011;Ausin et al 2012;Dowen et al 2012;Moissiard et al 2012;Stroud et al 2012Stroud et al , 2013Stroud et al , 2014Zhong et al 2012;Greenberg et al 2013;Law et al 2013;Zemach et al 2013). Since the original Watson and Crick strands, but not their reverse complements, were sequenced in these studies, only the telomeric C-rich strand was monitored to estimate methylation levels.…”
Section: Methodsmentioning
confidence: 99%
“…In silico analysis of telomeric DNA methylation Data from different genome-wide bisulfite sequencing studies were analyzed (Schmitz et al 2011;Ausin et al 2012;Dowen et al 2012;Moissiard et al 2012;Stroud et al 2012Stroud et al , 2013Stroud et al , 2014Zhong et al 2012;Greenberg et al 2013;Law et al 2013;Zemach et al 2013). Since the original Watson and Crick strands, but not their reverse complements, were sequenced in these studies, only the telomeric C-rich strand was monitored to estimate methylation levels.…”
Section: Methodsmentioning
confidence: 99%
“…S8). To assess whether RdDM also contributed, we examined the FBX expression patterns in Col-0 floral tissue abrogated in key RdDM components, AGO4, DRM2, and NRPE1 (22,25). A slight but significant increase in Low/Rare Exp FBX transcripts was observed that was not seen for High Exp transcripts, suggesting that RdDM helps transcriptionally suppress Low and Rare FBX genes (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…A method based on Fisher's exact test was used to identify differentially methylated regions (DMRs) (18), which are defined as regions that show significant differences in the statistical test (P < 0.05) and more than 1.5-fold changes in DNA methylation levels compared with wild-type plants. We identified 2,387 hypomethylated regions in the dtf1 mutant, compared with 4,780 and 4,884 in nrpd1 and nrpe1, respectively (Dataset S2).…”
Section: Dtf1mentioning
confidence: 99%